1958
DOI: 10.1515/znb-1958-0602
|View full text |Cite
|
Sign up to set email alerts
|

Vinylmercury Compounds

Abstract: Divinylquecksilber wurde durch Behandlung von Quecksilber (II) -chlorid oder bromid mit einem Überschuß von Vinylmagnesiumbromid dargestellt. Durch verdünnte Schwefelsäure wird die Vinylgruppe vom Divinylquecksilber als Äthylen abgespalten. Die Reaktion von Quecksilber (II) -halogeniden mit Vinylgrignard-Verbindungen in einem Verhältnis 1: 1 gibt die Verbindungen CH2: CHHgX (X=Cl, Br, J). Die Vinylquecksilberhalogenide werden durch Behandlung mit Äthyl- oder Phenyl-Grignardverbindungen in die gemischten Verbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Tributylstannane (Bu 3SnH), 4 methyl-(1), 5 ethenyl-(2a), 6 1-methylethenyl-(2b), 1-propenylmercury chlorides (2c) 7 and divinylmercury (3a-c) 8 were prepared as previously reported.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tributylstannane (Bu 3SnH), 4 methyl-(1), 5 ethenyl-(2a), 6 1-methylethenyl-(2b), 1-propenylmercury chlorides (2c) 7 and divinylmercury (3a-c) 8 were prepared as previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…13 -c). 8 In a 250 mL three-necked flask, the vinylmagnesium halide (0.1 mol) in THF (100 mL) was prepared as described above. The solution was cooled in an ice bath and a solution of HgCl 2 (13 g, 48 mmol) in dry THF (20 mL) was then slowly added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal complexes containing the perfluorovinyl (1,1,2-trifluoroethenyl) group, CFCF 2 , are a case in point; no structural data have been published despite the first examples of such materials being reported in the 1960s . By comparison structural data exist for a wide range of vinyl-containing compounds of main-group and transition-metal elements, and combined structural and theoretical modeling studies of divinylmercury and vinylmercury hydrides have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Substituent effects on the regioselectivity of alkene hydroboration are well understood. [20][21][22] Expanding on the work of Stone, 13,23 Brown and co-workers have demonstrated previously that trifluoropropene reacts with HBX 2 (X = Cl, Br, H) to give primarily Markovnikov substitution products with the selectivity being sensitive to the number of halogen ligands on the borane and ranging from 7:1 to >9:1. 12 Similarly, vinyl chloride has been proposed to react with BH 3 by Markovnikov addition.…”
Section: Alane Pathway (Concerted S N V)mentioning
confidence: 99%